2019
DOI: 10.1109/thms.2018.2885408
|View full text |Cite
|
Sign up to set email alerts
|

Co-Design of Musical Haptic Wearables for Electronic Music Performer's Communication

Abstract: Communication between performers is a fundamental aspect in music performance. A large number of electronic music instruments based on tangible and screen-based interfaces require a focused visual attention from performers while they are controlled. In certain stage and artistic configurations, this may be an obstacle to face-to-face creative interactions between coperformers and their collaborators. To address these issues, we adopted a user-centered design methodology to develop a novel class of IoT devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…To create a demonstration of interfaces that could provide vibrotactile cues useful to direct visually-impaired musicians during their practices, we let participants experience various MHWs that were developed in previous research (reported in [29] and [32]). These consisted in a belt equipped with four motors (see Figure 2a), a single self-contained armband equipped with two motors and two buttons (see Figure 2b), and a pair of armbands both equipped with two motors (see Figure 2c).…”
Section: Technology Demonstrations and Brainstorming Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To create a demonstration of interfaces that could provide vibrotactile cues useful to direct visually-impaired musicians during their practices, we let participants experience various MHWs that were developed in previous research (reported in [29] and [32]). These consisted in a belt equipped with four motors (see Figure 2a), a single self-contained armband equipped with two motors and two buttons (see Figure 2b), and a pair of armbands both equipped with two motors (see Figure 2c).…”
Section: Technology Demonstrations and Brainstorming Resultsmentioning
confidence: 99%
“…The advent of embedded and networking technologies has set the stage for the creation of new wearable devices for creative communication in musical contexts by leveraging the tactile channel. Recently, the Musical Haptic Wearables (MHWs) for performers have been proposed as instances of a wider family of Musical Things [29] within the Internet of Musical Things (IoMusT) paradigm [30]. Such a class of wearable devices targeting music performers encompasses haptic stimulation, gesture tracking, and wireless connectivity features.…”
Section: Introductionmentioning
confidence: 99%
“…In "The Elements of Fashion Style," Vaccaro et al [61] highlight language differences across fashion that frustrate users searching for outfit combinations. Recent wearables-related taxonomies span trends in design use and aesthetic experience [40], co-experience support [39], body placement zones [59], gestures [58], ergonomic comfort and wearability [25,67], virtual and in-person interactions [9,17], and privacy and user interactions [43,47].…”
Section: Taxonomiesmentioning
confidence: 99%
“…Various use cases were implemented, which leverage the smart qualities of the instrument. These include the programming of the instrument via applications for smartphones and desktop computer, as well as the wireless control of devices enabling multimodal performances such as screens displaying visuals, smartphones, and tactile devices used by the audience (Turchet & Barthet, 2019).…”
Section: Instances Of Smart Musical Instrumentsmentioning
confidence: 99%